Motorcycle fatalities revisited: A classical and Bayesian analysis - Richard Fowles; Peter D. Loeb; Chompoonuh K. Permpoonwiwat (The University of Utah, Department of Economics, 2017)
This paper examines the determinants of motorcycle fatality rates using panel data and classical and Bayesian statistical methods. It focuses on five variables in particular: universal helmet laws, partial helmet laws, cell phone use, suicidal propensities, and beer consumption. Universal helmet laws are found to be favored over partial helmet laws to reduce motorcycle fatality rates while cell phone use is found to be a significant contributor to motorcycle fatalities as is alcohol consumption. Suicidal propensities are also shown to contribute to these accidents.
Keywords: I18; C11; 330; motorcycle fatalities; cell phones; helmet laws; alcohol consumption; suicide; Bayesian econometrics